2022
DOI: 10.3389/fpsyt.2022.881541
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and psychometric properties of the affective lability scale-short form in Chinese adolescents

Abstract: ObjectivePrevious studies on the reliability and validity of the Affective Lability Scale short-form (ALS-SF) have only been evaluated in adults, which may not be able to generalize to the adolescent population. We aimed to examine the factor structure, the reliability and validity of ALS-SF among Chinese adolescents and construct an adolescent form of ALS (ALS-AF).MethodsA total of 1,439 middle school students were investigated with a broad survey including ALS-SF, Patient Health Questionnaire-9 (PHQ-9), Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Compared with the Chinese version of the ALS-SF validated in the Chinese adolescent population which removed three items (item 2, 4, 10) from the original scale due to non-significant associations with factors ( 21 ), our study found that the scale structure of the ALS-SF in individuals with mood disorders remained consistent with the original scale. We believe that such differences may result from the different sample population.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Compared with the Chinese version of the ALS-SF validated in the Chinese adolescent population which removed three items (item 2, 4, 10) from the original scale due to non-significant associations with factors ( 21 ), our study found that the scale structure of the ALS-SF in individuals with mood disorders remained consistent with the original scale. We believe that such differences may result from the different sample population.…”
Section: Discussionmentioning
confidence: 70%
“…Affective lability is one of the key features of mood disorder and has a significant correlation with the development of the disorders ( 2–4 ). While in adolescent, affective lability is more likely to be associated with personality types, life events, and external environment ( 21 ). In addition, the difference in age may have contributed to the difference in the understanding of items to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CV was assessed by factor loading, Composite Reliability (CR), and Average Variance Extracted (AVE) [ 28 ]. AVE refers to how much variation explained by potential factors comes from measurement error [ 28 , 29 ]. The larger the AVE is, the larger the percentage of variation explained by potential factors is, and the smaller the relative measurement error.…”
Section: Methodsmentioning
confidence: 99%